2013
DOI: 10.35609/gjbssr.2013.1.4(2)
|View full text |Cite
|
Sign up to set email alerts
|

Reward and Employee's Creativity: Case of Manufacturing Organization

Abstract: Objective - The main objective of this study is to investigatestrategic reward systems that are intrinsic and extrinsic reward for employees. The rewards address four areas that consist of compensation, benefits, recognition and appreciation. This study discussed whether the reward system gives more benefit to the organization and employees such as improving the employee level of creativity or vice versa. Methodology/Technique - This study is a correlational study where the researchers examined the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A research study by Rahim et al (2013) in the manufacturing industries in Shah Alam findings shows that rewards are key factors to the creativity or ideas of employees in administrative support personnel. However, Rahim et al (2013) study argues that the creativity of employees does not only depend on extrinsic rewards but also intrinsic rewards.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A research study by Rahim et al (2013) in the manufacturing industries in Shah Alam findings shows that rewards are key factors to the creativity or ideas of employees in administrative support personnel. However, Rahim et al (2013) study argues that the creativity of employees does not only depend on extrinsic rewards but also intrinsic rewards.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…A research study by Rahim et al (2013) in the manufacturing industries in Shah Alam findings shows that rewards are key factors to the creativity or ideas of employees in administrative support personnel. However, Rahim et al (2013) study argues that the creativity of employees does not only depend on extrinsic rewards but also intrinsic rewards. The study also found that creativity is not similar for everybody in the organization, as for that person have creativity that is different as they are hired by the organization to utilise the benefits possessed by employees to attain its business goals and objectives.…”
Section: Empirical Reviewmentioning
confidence: 99%